The linkage between regional economic indexes and tax bases: Evidence from New York - Jason Bram; Andrew Haughwout; James Orr; Robert Rich; Rae Rosen (Federal Reserve Bank of New York, 2004)
This paper examines the linkage between economic activity and tax revenues for New York State and New York City. Drawing upon the methodology of Stock and Watson, we use a dynamic single-factor model to estimate indexes of coincident economic indicators. We also construct measures of the sales and withholding tax bases. To conduct an empirical analysis of the relationship between the indexes of economic activity and the tax base series, we use vector autoregression and error correction models. The results provide strong evidence that the coincident indexes contain useful information for explaining monthly growth in the tax bases. However, much less evidence exists of a statistically significant linkage from the tax bases to the coincident indexes.
Keywords: C32; E32; H71; 330; Regionale Wirtschaftskraft; Wirtschaftslage; Steueraufkommen; New York (NY)